Studies on the potential risk of amyloidosis from exposure to silk fibroin. (21st November 2016) - Tsukawaki, Satomi; Murakami, Tomoaki; Suzuki, Kazuhiko; Nakazawa, Yasumoto
Abstract: Amyloid A (AA) amyloidosis can be induced by the administration of amyloid fibrils to animals under inflammatory conditions. Silk fibroin (SF) is a main component protein of bombic silk and has amyloid-like features. The amyloidogenesis of SF solution in mice has been previously reported. Recently, the biochemical properties of silk have attracted increasing attention, and research and development have been undertaken regarding applications other than as a clothing material. However, the risk of AA amyloidosis from exposure to SF-related products is unknown. In this study, we examined the amyloidogenesis of several SF-related products that vary in preparation method or route of injection in a mouse model of amyloidosis. The results revealed that amyloid deposits were rarely observed in mice exposed to SF solution or feed supplemented with SF powder. On the other hand, heavy amyloid deposits were observed in some mice implanted with SF non-woven fabric by abdominal operation. Congo red staining of SF solutions under polarized light and electron microscopy indicated that SF solution in this study had no amyloid-like structures. We found that SF-related products occasionally promote amyloidogenesis, but have a low potential for amyloidosis.